A haunted beast: Targeting STAT5BN642H in T-Cell Neoplasia. (4th May 2018) - Pham, Ha Thi Thanh; Hengstschläger, Markus; Moriggl, Richard
ABSTRACT: The somatic hot spot mutation STAT5BN642H was found in many T cell leukemia/lymphoma patients. We generated and analyzed a transgenic mouse model with hematopoietic STAT5BN642H expression that caused aggressive T-cell leukemia/lymphomas. Herein, we discuss the scientific merit of our model and its relevance for pre-clinical studies.